The Use of Slang Words Among Junior High School Students in Everyday Conversation (A case study in the ninth grade students of a junior high school in Bandung) - Widya Pradianti (Passage, 2013)
The study is entitled "The Use of Slang Words among Junior High School Students in Everyday Conversation." It aims to investigate slang words used by the ninth grade students. This study also investigates the morphological processes involved in slang words and the reasons why the students use them in their everyday talk. The collected data from questionnaires and interviews were categorized into the types of slang words and analyzed in terms of their morphological processes by using a method of analysis based on theories as proposed by Yule (1985), Potter (1975), O'Grady and Guzman (1996), and Gerber (1968). These data were calculated in terms of frequency presented in tables and charts. The findings show that there are eleven groups of morphological processes in this study. Coinage is the most frequently used with 30.56%, followed by blending with 20.14% and borrowing with 13.19% words. Furthermore, there are some reasons influencing appearances of slang words, namely students want to say something in an easy way, show their anger, make other people confused, and want to have fun and laugh. Thus, future researchers are recommended to conduct studies on different slang users in different settings because slang changes and increases through time.Keywords: slang words, morphological processes, coinage, blending, borrowing.